17.1 %‐Efficient Eco‐Compatible Organic Solar Cells from a Dissymmetric 3D Network Acceptor. (10th December 2020) - Chen, Hui; Lai, Hanjian; Chen, Ziyi; Zhu, Yulin; Wang, Huan; Han, Liang; Zhang, Yuanzhu; He, Feng
Abstract: To elevate the performance of polymer solar cells (PSC) processed by non‐halogenated solvents, a dissymmetric fused‐ring acceptor BTIC‐2Cl‐γCF3 with chlorine and trifluoromethyl end groups has been designed and synthesized. X‐ray crystallographic data suggests that BTIC‐2Cl‐γCF3 has a 3D network packing structure as a result of H‐ and J‐aggregations between adjacent molecules, which will strengthen its charge transport as an acceptor material. When PBDB‐TF was used as a donor, the toluene‐processed binary device realized a high power conversion efficiency (PCE) of 16.31 %, which improved to 17.12 % when PC71ThBM was added as the third component. Its efficiency of over 17 % is currently the highest among polymer solar cells processed by non‐halogenated solvents. Compared to its symmetric counterparts BTIC‐4Cl and BTIC‐CF3 ‐γ, the dissymmetric BTIC‐2Cl‐γCF3 integrates their merits, and has optimized the molecular aggregations with excellent storage and photo‐stability, and also extending the maximum absorption peak in film to 852 nm. The devices exhibit good transparency indicating a potential utilization in semi‐transparent building integrated photovoltaics (ST‐BIPV). Abstract : A dissymmetric fused‐ring acceptor BTIC‐2Cl‐γCF3 with chlorine and trifluoromethyl end groups give a power conversion efficiency (PCE) of over 17 % which is the highest among polymer solar cells processed by halogen‐free solvents. Dissymmetric chlorination and trifluoromethylation is a practical approach towards a low band‐gap acceptor for eco‐compatible processed photovoltaic applications.